Continuing Trauma Care After Discharge, the Experience of Outpatient Trauma Clinics in British Columbia. Issue 2 (March 2018) - Tuyp, Benjamin; Hassani, Kasra; Thurston, Cynthia; Fyvie, Kathleen; Constable, Lisa
Abstract : The recovery process from traumatic injuries, and the potential for complications, extends beyond the time of hospital discharge. In 2014, the Fraser Health Trauma Network established outpatient clinics to provide follow-up care for trauma patients after discharge from hospital. The following research questions were asked: Which services were commonly performed by our trauma clinics and how satisfied were patients with the care they received at our clinics? A survey was distributed to patients after their clinic visit to assess overall satisfaction and areas for improvement. A retrospective medical record review was performed to illustrate and quantify the interventions provided during clinic visits. During the first 22 months of clinic operation, a total of 412 appointments were scheduled and the attendance rate was 88%. The provided services included obtaining additional imaging (41% of visits), providing wound and brace care (16%), and initiating referrals to specialists (12%). Seventy-seven patient satisfaction surveys were returned during the study period, 34 in 2014 and 43 in 2015. Seventy-four percent of respondents strongly agreed, and 21% agreed that they were satisfied with the care they received in the clinic. Ninety percent found their visit helpful, and only 10% reported having additional medical issues that were not addressed during the appointment. At trauma clinic follow-up, discharged patients have ongoing care requirements, including a need for further investigation, specialist referral, and wound or brace issues that are likely to benefit from specialist trauma care. Patients were satisfied with the care provided by a postdischarge trauma clinic.